Imperative of Viable Learning Environment for Early Childhood Education: A Literature Review - Makeleni, Sive; Ndu, Onyinyechi Glory (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
This paper examines the vital role of the early childhood learning environment as conducive learning environments are pivotal to promoting the holistic development of a child. It argues that early childhood development is a critical period that fundamentally influences intellectual, social, emotional, and physical development. Hence, the learning environment at the unique stage of education must be adequate, vibrant, and supportive for the optimal realisation of educational goals.  The study utilized a literature review methodology, to identify and synthesize critical issues in early childhood education learning environment. In this regard, about 50 peer-reviewed journal articles indexed by Scopus, DOAJ, and EBSCO were reviewed. It revealed that a quality learning environments and physical exercise are essential conditions required to early childhood cognition. Educators should consciously provide a robust and dynamic learning environment that promotes different learning styles to attain well-rounded early childhood educational development of the child.